(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
Terminology is defined as a set of terms interacting with the system of concepts of a particular science. Any system of concepts corresponds to a certain system of terms. Terminological systems develop together with the progress of science. Terms are introduced differently from common words, and their use is subject to some degree of control.